Negotiations Framework for Monitoring the Sustainability of Interoperability Solutions - Coutinho, C.; Cretan, A.; Jardim-Goncalves, R. (Proceedings of the 4th International IFIP Working Conference on Enterprise Interoperability (IWEI 2012), 2012)
The competition inherent to globalisation has led enterprises to gather in nests of specialised business providers with the purpose of building better applications and provide more complete solutions. This, added to the improvements on the Information and Communications Technologies (ICT), led to a paradigm shift from product-centrism to service-centrism and to the need to communicate and interoperate. Traditional segments like banking, insurance and aerospace subcontract a large number of Small and Medium Enterprises (SMEs) that are undergoing this change, and must ensure the criticality and accuracy of their business is not affected or impacted in any way. This paper proposes a methodology and a framework that provide critical businesses a control mechanism over the interoperability solutions in place on their subcontracted enterprises, imposing negotiations which formalise the solutions applied. It then focuses on its application on the business case of the Concurrent Design Facility of the European Space Agency (ESA-CDF).